RANCANG BANGUN SENSOR BH1750 BERBASIS MIKROKONTROLLER SEBAGAI FOTOTERAPI PADA PENDERITA HIPERBILIRUBIN/BAYI KUNING - Yuyun Azizah Kudadiri; Fitria Priyulida (JURNAL MUTIARA ELEKTROMEDIK, 2021)
Phototherapy equipment is one type of physiotherapy equipment that is used to treat patients with Neonatal Jaundice. This tool works like an incandescent lamp in general, transmitting blue light directly to the baby's body which will then help reduce the amount of bilirubin that has accumulated in the baby's skin layer. born. This situation is experienced by many babies born prematurely and also babies who are breastfed late. Hyperbilirubinemia can be easily treated by the aforementioned light therapy. The light given by the tool is one type of light that is harmful to vision, so that in the process of irradiating the baby, an eye patch will be worn to protect the retina of the eye which is still in the process of being perfected. In the process, the author added a light reading feature/ photometer to measure the amount of light produced by the phototherapy device. The photometer is made by utilizing the BH1750 sensor with the function of reading light rays (any) in lux units, so that users can easily find out how many doses of light are produced in the therapy process.The measurement results from the photometer are displayed on the LCD, with the measurement of the light value in lux units of 266.67 Lux. The measurement results are stable with the irradiation distance between the lamp and the location of the sensor as much as 30 cm.